Commentary: Overview of Developmental Perspectives on Creativity and the Realization of Potential. Issue 151 (March 2016) - Runco, Mark A.
Abstract: The articles in this issue of New Directions for Child and Adolescent Development nicely summarize recent findings about creativity and development. This commentary underscores some of the key ideas and puts them into a larger context (i.e., the corpus of creativity research). It pinpoints areas of agreement (e.g., the need to take both generative and convergent processes into account when examining developmental changes in creative behavior) but balances this with a discussion of concerns. These include (a) problems with the concept of Big C creativity, as it may confound the realization of creative potential, (b) lack of attention given to cultural relativity, and (c) inappropriate testing of divergent thinking. Still, the progress in the research is clear and the fulfillment of creative potentials increasingly likely.